Mapping the MPEG-4 visual texture decoder a system-level design technique based on heterogeneous platforms. - Zhe Ma (IEEE Signal processing magazine)
This article presents automated techniques supporting the design-time scheduling phase of a unique approach for managing concurrent tasks of dynamic real-time applications mapped on a heterogeneous platform with different types of software and hardware components. This approach is based on design-time exploration, which results in a set of schedules and assignments for each task, represented by Pareto curves. At run-time, a low complexity scheduler selects an optimal combination of working points, exploiting the dynamic and nondeterministic behavior of the system. The combined approach leads to significant overall power savings compared to state-of-the-art dynamic voltage scaling techniques. The design-time generated Pareto curves can also be used by the application designer to effectively make quantitative tradeoffs between system cost and performance.